Ways of Introduction of Information Technologies in Training of Music Teachers: (Chinese and Ukrainian experience) - Fan, May; Matvieieva, Olha (Professional Art Education, 2021)
The purpose of the article is to analyze the areas of research and experience in implementing information technology in the training of music teachers in Ukraine and China. Methodology. In Ukraine, the importance of the introduction of information technology is supported at the state level. To analyze the introduction of information technology in the training of music teachers were analyzed: the Law "On the National Informatization Program", the Order of the Ministry of Education and Science of Ukraine "Some issues of distance learning", the Concept of distance education in Ukraine and the Concept of media education. The study revealed various aspects of the use of information technology in education in Ukraine. Ukrainian scholars emphasize the importance of using information technology in the educational process because of changing the basic educational paradigm: if before the teacher was the main source of professional information, which led to reproductive teaching methods, now the teacher’s function is different, he must teach students to navigate in the information environment, to develop his creative and intellectual abilities. The application and introduction of information technologies and methods in the educational process of teacher training in music art has been studied in the works of Yu. Dvornyk (2015), L. Bondarenko (2019), L. Gavrilova (2016) and others. Scientific novelty. A comparative model of the use of information technology in the training of music teachers in China is presented. This issue is related to the unified system of qualification and educational standards and curricula for the training of music teachers developed by the Ministry of Education of the PRC. In the researches of Chinese scientists the following main features of informatization in the training of music teachers have been identified: dissolves the boundaries of the media and personalizes music; evaluation of music becomes the beginning of stimulating its creation, many people become participants in musical works; provides students with a wide range of ways to disseminate and exchange information for a creative desire to express themselves in the creation of musical works; leads to the transformation of traditional forms of teaching music; accelerates the speed of music distribution; violates a clear distinction between music creators and listeners, as listeners can also become creators. Conclusions. A brief review of legislation, regulations and research of Ukrainian scientists allows us to conclude about the systematic, planned, multi-vector activities for the improvement and development of information technology in education, in the training of music teachers. The outlined ways of introducing information technologies in the training of music teachers in Ukraine and China testify to the widespread development by Chinese scientists of problems of informatization of art education, covering issues of historical preconditions, formation, development and forecasting of information technology integration in music teachers. On the other hand, in our country, the work is focused more on systematic, planned, multi-vector activities to improve and develop information technology in the training of music teachers.